Nilai Moral dan Budaya dalam Tradisi Mappacci pada Pernikahan Masyarakat Bugis di Kelurahan Bitoa Kecamatan Manggala Kota Makassar - Friselia Ifonita; Mr. Bahri (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This research aims to determine the moral and cultural values in the mappacci tradition at weddings of the Bugis community, to understand the procession of the mappacci tradition of the Bugis community, to describe the moral values found in the mappacci tradition of the Bugis community and the meaning of society in the mappacci tradition at weddings of the Bugis community. The results of this research show that based on the existence of the mappacci tradition which is slowly but surely starting to fade, there are still some Bugis people in Bitowa Village, Manggala District who continue to maintain the implementation of the mappacci tradition in weddings. Although it does not mean that their knowledge of the moral values contained in the Mappacci tradition itself is more obedient to customs alone.